ANALYSIS OF CUSTOMER SATISFACTION OF KINGKOIL MATTRESS PRODUCTS BASED ON CUSTOMER PERCEPTION USING IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Chusnul Chotimah; Agus Baktiono; Elok Damayanti (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to analyze customer satisfaction based on perceptions of brand image, product quality, price, promotion, and distribution. This research was conducted at KingKoil Mattress Boutique Tunjungan Plaza Surabaya. Data collection was carried out to support this study using convenience sampling techniques for 50 respondents and fill out questionnaires. The method used in this study is Importance Performance Analysis (IPA). Based on the results of Importance Performance Analysis, the level of performance and the customer satisfaction are very satisfactory with an average value above 93.75%. This means customers are very satisfied.